Influence of android-based “Healthy Menstruation” application on menstrual knowledge in adolescent girls - Suptiani, Laila Putri; Kurnia, Herni (Poltekkes Kemenkes Yogyakarta, 2024)
Many women have menstrual problems, among them menstrual pain known as dysmenorrhea. Education and knowledge of using learning media are important to improve the management of dysmenorrhea. The used of smartphone applications for menstrual tracking was popular among adolescents for their convenience and privacy. However, these studies often focus on broader reproductive health topics rather than specific menstrual knowledge. The aim of this research was to determine the influence of implementing “Healthy Menstruation” application on the knowledge of adolescent girls about menstruation.The research method used in this study was a quasi-experimental design with a one-group pretest-posttest design. Independent variable in this research was android based “Healthy Menstruation” Application, while dependent variable in this research was knowledge. The results of the study using the Wilcoxon test showed that there was an influence of the application on the knowledge of adolescents with a p=0.000. here was an influence of the “Menstrual Health” application on the knowledge of adolescents may change as to improve the literacy of female adolescent.